Assessment of the precision of data collected about the traffic accidents with property damage only in claim handling process by insurance companies - Ernits, Erik; Antov, Dago; Kott, Anton (Transport, 2017)
The number of serious road traffic accidents is decreasing in all European countries. Based on the trends and directions in the past it may be predicted that in longer perspective the number of serious road traffic accidents will decrease remarkably. This will create a situation where it is more and more difficult to ensure the reliability of traffic safety analyses performed by statistical methods. There are two possibilities to decrease the problem: either to carry out in-depth investigations of serious road traffic accidents and/or investigate also Property Damage Only (PDO) traffic accidents and traffic conflicts in addition to serious traffic accidents. The key issue in using the PDO accident data is its precision. The present paper is attempting to enlighten the area, and assess the quality of data of PDO road traffic accidents collected by insurance providers by example of Estonia. The survey results show that in spite of certain shortcomings, the PDO road traffic accident data collected by insurance provider is valuable to be used in traffic safety analyses. First published online: 09 May 2014